Efektifitas Model Blended Learning Terhadap Hasil Belajar Matematika Siswa SMP - Gunawan Gunawan; Murtalib Murtalib; Sowanto Sowanto (Program Studi Pendidikan Matematika, 2022)
The purpose of this study was to compare the effectiveness of learning by using short to determine the effectiveness of learning with offline and online methods (Blended) on improving students' mathematics learning outcomes. The sample in this study was class VII7 which was taught using the Blended method and VII6 using the conventional method. Sampling using simple random sampling technique. This research an experimental study with a quasi-experimental setting of the pre-test posttest design model, namely research that provides test questions before and after learning using the Blended learning method and the Conventional Method. The research instrument used in this study was a question of pre-test and post-test in the form of a description of the material Numbers. The technique of collecting data is by using the technique of documenting the results of the pre-test and post-test given to both the experimental and control classes. The data analysis technique used the inferential analysis technique of the independent sample t test by first testing its normality and homogeneity. Based on the results of the output normality test of variance using the Shapiro-Wilk test, the significance value for the experimental class is 0.060 and the control class is 0.135. Because the significance value of the two classes is more than 0.05, it can be said that the control class and the experimental class are normally distributed. For the results of the homogeneity test, it was obtained that the significance value was above the homogeneity test on the variance using the Levene. the significance value is 0.274. Because the significance value is greater than 0.05, it can be concluded that the control class and experimental class students come from populations that have the same variance, or the two classes are homogeneous. based on the results of hypothesis testing conducted with the NGain test through the SPSS 20.0 for Windows program, the learning outcomes obtained in the form of percentages between the experimental class and the control class. Based on the output results in table 13, it is found that the average NGain score for the experimental class with a 95% confidence level is NGain = 60.17% with a minimum NGain score = 44.44 and a maximum NGain score is 76.1. for the control class, the average value of NGain in the control class is obtained with a 95% confidence level, NGain = 43.71% with a minimum NGain score = 21.43 and a maximum NGain score is 72.22. Based on these results, it can be concluded that based on the criteria for determining effectiveness in table 12 above, learning using the blended method for class VII students of SMPN 2 Bima City is in the category of being quite effective in improving learning outcomes. Keywords: effectiveness, Blended Method, Leraning Outcomes.